2019
DOI: 10.3892/ol.2019.10553
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TRA2B in endometrial carcinoma and its regulatory roles in endometrial carcinoma cells

Abstract: Expression levels of Transformer 2 protein homolog beta (TRA2B) in patients with endometrial carcinoma were assessed to investigate the impact of TRA2B on endometrial carcinoma cells. Furthermore, we analyzed the expression of several genes in the tissue samples from patients with endometrial cancer (EC) to identify whether cancer related genes we chose are differently expressed between the endometrial carcinoma tissues and adjacent normal tissues. The results of RT-qPCR analysis, western blot technology and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Several studies have revealed that TRA2B can inhibit cellular apoptosis or promote invasion in several cancers [ 19 , 20 ]. Both the TRA2B messenger RNA (mRNA) and Tra2β protein levels are increased in many cancers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that TRA2B can inhibit cellular apoptosis or promote invasion in several cancers [ 19 , 20 ]. Both the TRA2B messenger RNA (mRNA) and Tra2β protein levels are increased in many cancers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transformer 2β (Tra2β) contains two serine/arginine domains and an RNA recognition motif, and it functions as a sequence-specific pre-mRNA splicing enhancer 9 , 10 . Overexpression of the Tra2β protein is associated with the development of several cancers 11 14 . We previously reported that the protein and mRNA levels of Tra2β were upregulated in colon cancer cells, and silencing of Tra2β decreased colon cancer cell proliferation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study confirmed the regulatory role of TRA2B in EC with overexpression of TRA2B clearly correlating with increased proliferation of EC cells. In addition, inhibition of TRA2B expression by siRNA reversed these effects and increased apoptosis ( 17 ), suggesting not only prognostic role of TRA2B expression, but also making this gene a potential target for development of EC treatment. Another possibility is the presence of SOX17.…”
Section: Introductionmentioning
confidence: 99%